Integrating solar photovoltaic energy conversion systems into industrial and commercial electrical energy utilizationA survey - K P.; Govindarajan U.; Ramachandaramurthy V.K.; T S.O.S.; Jeevarathinam B. (Elsevier B.V., 2023)
Commerce; Electric energy storage; Energy management systems; Energy utilization; Environmental impact; Environmental impact assessments; Environmental technology; Information management; Photovoltaic cells; Solar concentrators; Solar energy; Interpretations and recommendations; Market pricing; Solar PV systems; Technical issues; Technology trends; Solar power generation